Нормування дизельного палива на тягу поїздів для маневрових тепловозів - Гащук, Роман Андрійович; Hashchuk, Roman Andriiovych (Національний університет "Львівська політехніка", 2024)
Однією з важливих галузей матеріального виробництва в країні є транспорт, а однією з важливих галузей транспорту є залізничний транспорт. При цьому він являється одним з найбільших споживачів паливно-енергетичних ресурсів. Щорічно він споживає більше п’ятисот тон дизельного палива. Зростання цін на нього веде до збільшення витрат на продукцію промисловості України, та витрат на технічну експлуатацію залізничного транспорту. При експлуатації тепловозів, навіть в одному регіоні експлуатації, змінюються, як його технічний стан, так і стан інфраструктури, а відповідно і змінюється витрата палива. Це потребує уточнення норм витрат палива тепловозами в конкретному регіоні експлуатації для конкретного тепловоза. Тому питання раціоналізації витрат паливо-енергетичних ресурсів є завжди актуальною проблемою для залізничного транспорту в цілому і для тепловозів в локомотивних депо в тому числі. Це підтверджує практичну актуальність обраної тематики. Об’єкт дослідження – робота тепловозів ЧМЕ3 під час виконання маневрової роботи Предмет дослідження – методи нормування витрат палива на маневрову роботу. Мета дослідження – є зменшення затрат на маневрову роботу тепловозами ЧМЕ3 за рахунок раціонального нормування палива. За результатами кваліфікаційної роботи виконано такі задачі досліджень: • проведено аналіз заходів економії палива на залізничному транспорті; • розглянуто існуючі методи розрахунку норм витрат палива на залізниці; • розроблені алгоритм і модель встановлення норм витрати палива на маневрову роботу; • виконано нормування витрат палива на маневрову роботу для тепловозів ЧМЕ3 для заданої дільниці обслуговування. Встановлено, що норми витрат для тепловозів, які проводять маневри або знаходяться в простої встановлюють на 1 годину роботи. При цьому дані норми являються поопераційними і корегуються в залежності від сезону для кожного типу тепловозів окремо. Розрахунок питомих витрат палива на маневрову роботу проводиться шляхом проведення дослідних поїздок з вагоном-лабораторією. Визначено основні формули для розрахунку показників, які задіяні при визначенні норм витрат палива на маневрову роботу. Для маневрової роботи на станції визначені фактичні та розрахункові погодинні витрати палива. На їх основі розраховані похибки між ними та дані рекомендації по обгрунтуванню зменшення норм витрати палива тепловозами типу ЧМЕ3 на виконання маневрових робіт.

One of the important branches of material production in the country is transport, and one of the important branches of transport is railway transport. At the same time, it is one of the largest consumers of fuel and energy resources. Every year it consumes more than five hundred tons of diesel fuel. The increase in its prices leads to an increase in the costs of Ukrainian industry products and the costs of technical operation of railway transport. When operating diesel locomotives, even in one region of operation, both their technical condition and the state of the infrastructure change, and accordingly, fuel consumption changes. This requires clarification of the norms of fuel consumption by diesel locomotives in a specific region of operation for a specific diesel locomotive. Therefore, the issue of rationalizing the costs of fuel and energy resources is always an urgent problem for railway transport in general and for diesel locomotives in locomotive depots in particular. This confirms the practical relevance of the chosen topic. The object of the study is the operation of diesel locomotives ChME3 during shunting work The subject of the study is methods of fuel consumption rationing for shunting work. The purpose of the study is to reduce the costs of shunting work by diesel locomotives ChME3 due to rational fuel rationing. According to the results of the qualification work, the following research tasks were completed: • an analysis of fuel saving measures in railway transport was carried out; • existing methods of calculating fuel consumption rates on the railway were considered; • an algorithm and model for establishing fuel consumption rates for shunting work were developed; • fuel consumption for shunting work for diesel locomotives ChME3 for a given service area was normalized. It was established that the consumption rates for diesel locomotives that perform shunting or are idle are set for 1 hour of operation. At the same time, these rates are operational and are adjusted depending on the season for each type of diesel locomotive separately. The calculation of specific fuel consumption for shunting work is carried out by conducting experimental trips with a laboratory car. The main formulas for calculating the indicators involved in determining fuel consumption rates for shunting work have been determined. For shunting work at the station, the actual and estimated hourly fuel consumption rates have been determined. Based on them, the errors between them have been calculated and recommendations have been given to justify the reduction of fuel consumption rates for diesel locomotives of the ChME3 type for shunting work.
Rationing of diesel fuel for train traction for shunting locomotives
Keywords: 6.273.00.02; норма витрати палива; паливно-енергетичний ресурс; тепловоз ЧМЕ 3; маневрова робота; питома витрата палива; ChME 3 locomotive; wheelset tire; temperature field; thermal stresses and deformations; heating temperature